Resolution of Fenfluramine-associated pulmonary arterial hypertension in Lennox-Gastaut syndrome: A case report and literature review - Rebecca Strafella; Richard Wang; Marissa Petchpradub; Ariel Sacknovitz; Patricia E. McGoldrick; Steven M. Wolf (Epilepsy & Behavior Reports)
Fenfluramine is a medication originally approved for weight loss before being withdrawn for an association with the development of pulmonary arterial hypertension (PAH) and cardiac valvulopathy. Interest in fenfluramine at lower doses has re-emerged for treatment of drug-resistant epilepsy (DRE). Here, we present a case of a patient with Lennox-Gastaut Syndrome (LGS) treated with fenfluramine with development of PAH and tricuspid regurgitation that resolved upon discontinuation.A 4-year-old female with LGS refractory to anti-seizure medications and neuromodulation was screened by echocardiogram and started on fenfluramine due to persistent seizures. At 6 months, the patient developed asymptomatic PAH and tricuspid regurgitation. The medication was discontinued, and 2 months post-cessation, an echocardiogram showed PAH and cardiac valvulopathy resolution. The patient was restarted on fenfluramine due to seizures, and follow up exam with echocardiogram 6 months following retrial showed no PAH recurrence.We present a case of LGS treated with fenfluramine complicated by PAH until cessation, with subsequent retrial tolerated. This is the first pediatric patient to develop cardiac abnormalities during treatment with fenfluramine, which has been demonstrated to be efficacious and safe in DRE at lower doses than those utilized for weight loss. With appropriate screening, fenfluramine should be considered as an adjunct treatment option for DRE in select patients, and PAH as a complication of the medication may be reversible and non-recurrent on retrial.